Elemental Analysis : An Introduction to Modern Spectrometric Techniques - Schlemmer, Gerhard; Balcaen, Lieve; Hinds, Michael W.; Todolí, José Luis (De Gruyter Textbook, 2019)
Elemental Analysis is an excellent guide introducing cutting-edge methods for the qualitative and quantitative analysis of elements. Each chapter of the book gives an overview of a certain technique, such as AAS, AFS, ICP-OES, MIP-OES, ICP-MS and XRF. Readers will benefit from a balanced combination of theoretical basics, operational principles of instruments and their practical applications.